Development of a strategy and structure for land suitability evaluation for Eritrea - Laker, M.C. (Michiel Christiaan), 1939- (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Land Use Planning))--University of Pretoria, 2007.